Intravascular Residence Time Determination for the Cyanide Antidote Dimethyl Trisulfide in Rat by Using Liquid-Liquid Extraction Coupled with High Performance Liquid Chromatography - Deepthika De Silva; Steven Lee; Anna Duke; Siva Angalakurthi; Ching-En Chou; Afshin Ebrahimpour; David E. Thompson; Ilona Petrikovics (Journal of Analytical Methods in Chemistry)
These studies represent the first report on the intravascular residence time determinations for the cyanide antidote dimethyl trisulfide (DMTS) in a rat model by using high performance liquid chromatography coupled with ultraviolet absorption spectroscopy (HPLC-UV). The newly developed sample preparation included liquid-liquid extraction by cyclohexanone. The calibration curves showed a linear response for DMTS concentrations between 0.010 and 0.30 mg/mL with R2 = 0.9994. The limit of detection for DMTS via this extraction method was 0.010 mg/mL, and the limit of quantitation was 0.034 mg/mL. Thus this calibration curve provided a tool for determining DMTS in the range between 0.04 and 0.30 mg/mL. Rats were given 20 mg/kg DMTS dose (in 15% Polysorbate 80) intravenously, and blood samples were taken 15, 60, 90, 120, and 240 min after DMTS injections. The data points were plotted as DMTS concentration in RBCs versus time, and the intravascular residence time was determined graphically. The results indicated a half-life of 36 min in a rat model, suggesting that the circulation time is long enough to provide a reasonable time interval for cyanide antagonism.